Pengaruh Pemberian POC Nasa dan Pemangkasanstolon Terhadap Pertumbuhan dan Produksi Tanaman Stroberi ( Fragaria sp.) di Berastagi Kabupaten Karo - Tafonao, Duhusokhi; Harahap, Rahmaniah; Br. Jabat, Yelfi Yana Linda (UNIVERSITAS LABUHANBATU, 2023)
Strawberries are a plant that has various benefits. The fresh fruit and attractive color make strawberries very popular with all groups (Oktarina et al., 2017). In conventionally grown strawberry plants, flowers and stolons generally appear around 8 weeks after planting (WAP), and one parent plant is only able to produce 3 to 4 stolons. This research was carried out in Sempajaya Village, Berastagi District, Karo Regency, North Sumatra, at an altitude of 1,000–1,300 meters above sea level. This research was started in June–August 2023. The research method used was a randomized group design (RAK) with two factors, including: Factor I: Giving Nasa Liquid Organic Fertilizer (P), which consists of 3 levels: P0: control, P1: 2.5 ml, P2: 5 ml, and P3: 7.5 ml. Factor II: Stolon pruning (S) consists of 3 levels, namely: S0: no pruning; S1: 1 pruned stolon; and S2: 2 pruned stolons. From the results of this research, it can be concluded that the single effect of giving Nasa liquid organic fertilizer is significantly different on the number of fruit in harvest 1 and harvest 3, but is not significantly different on the number of fruit in harvest 2, plant height (cm), number of leaves (strands), and fresh weight of sample plants; the single effect of stolon pruning was not significantly different on plant height (cm), number of leaves (strands), number of fruit, and fresh weight of sample plants; and The interaction effect of giving Nasa liquid organic fertilizer and pruning stolons was not significantly different on plant height (cm), number of leaves (strands), number of fruits, and fresh weight of sample plants (g).